The Impact of Inflation on Inequality and Income Distribution in Iran by Emphasizing Expenditure Centile - Shams Tarnabi, Farzaneh; Raghfar, Hossein (International journal of industrial engineering and operational research, 2024)
This paper assesses the significance of the impact of seigniorage (the income generated by the government through money printing, which is a crucial pathway for inflation due to budget deficits covered by money printing, leading to inflationary taxation) and inflationary tax on inequality, using a combined model from 1996 to 2023. It highlights the varying effects of inflation on different income groups, particularly the role of government income from money creation in exacerbating inequality. The results indicate that seigniorage increases inequality, as it affects income groups differently, with lower-income groups being more vulnerable than higher-income groups. Consequently, an increase in inflationary taxation further heightens inequality.